2018
DOI: 10.1016/j.sjopt.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Does the addition of hyaluronidase improve the quality of peribulbar anesthesia in cataract surgery? – A randomized double blinded study

Abstract: Hyaluronidase is not an essential adjuvant for peribulbar block for cataract surgeries. Appropriate deposition of a smaller volume of anesthetic agent and adequate ocular massage provide adequate and safe anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In this study, all the cases were performed under peribulbaranesthesia, which is the primary technique for achieving ocular akinesia across the Indian subcontinent. [ 33 ] However, we believe this method has a high risk of complications, such as globe perforation, as it requires blind instrumentation. [ 34 ] Hence currently, we perform the majority of phacoemulsifications under topical anesthesia, and if required an akinesia sub-tenon block is adopted.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all the cases were performed under peribulbaranesthesia, which is the primary technique for achieving ocular akinesia across the Indian subcontinent. [ 33 ] However, we believe this method has a high risk of complications, such as globe perforation, as it requires blind instrumentation. [ 34 ] Hence currently, we perform the majority of phacoemulsifications under topical anesthesia, and if required an akinesia sub-tenon block is adopted.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Although several trials have suggested beneficial effects of RAI with hyaluronidase, including more rapid block onset, better akinesia, and better analgesia, others failed to show convincing differences in clinical efficacy. 2,[7][8][9][10][11][12] Despite its disputed clinical efficacy, hyaluronidase use is very common and several clinical preparations are commercially available. Adding hyaluronidase to RAI solutions reduces the effective concentration of the anesthetic; increases the complexity of mixing the anesthetic cocktail, introducing the possibility of a compounding error; increases cost; and may require a licensed compounding pharmacy for regulatory compliance.…”
Section: Introductionmentioning
confidence: 99%
“…46 Although several trials have suggested beneficial effects of RAI with hyaluronidase, including more rapid block onset, better akinesia, and better analgesia, others failed to show convincing differences in clinical efficacy. 2,712…”
Section: Introductionmentioning
confidence: 99%
“…Ibrahim et al [1] did not use midazolam in systemic form. Hyaluronidase was also tested by Swati et al [2] in a randomized double-blind study but did not prove to be beneficial in any sense. Rocuronium, a neuromuscular blocking agent, was also tried by Patil et al [3] and found to have a beneficial effect on the onset of akinesia but no effect on anesthesia.…”
mentioning
confidence: 99%
“…All these studies[1234] have been done in cataract surgery, which generally gets over in few minutes. Other ocular surgeries that take more time are vitreo-retinal surgery, keratoplasty, oculoplasty, etc., Early onset, prolonged duration of PA, and non-requirement of a supplementary block will be very useful in such surgeries.…”
mentioning
confidence: 99%